Manoeuvring Through the Crisis: Labour Market and Social Policies During the COVID-19 Pandemic - Werner Eichhorst; Paul Marx; Ulf Rinne (Intereconomics, 2020)
The unprecedented COVID-19 pandemic has a severe impact on societies, economies and labour markets. However, not all countries, socio-economic groups and sectors are equally affected. Part of this disparity can be related to the different role and extent of short-time work, which is now being used more widely than during the Great Recession. Furthermore, unemployment benefits have been made more generous in many countries. While it is still too early to assess the relative success of national strategies to cope with the pandemic and to revitalise the labour market as well as to evaluate the medium-term fiscal viability of different support measures, a few policy directions become apparent. These include the use of digital tools to increase resilience against economic shocks, the longer-term perspective of short-time workers in the current crisis, social protection for self-employed workers that is robust to economic crises and resilient models for school-to-work transitions of younger workers.
Keywords: 330; Coronavirus; Epidemie; Arbeitsmarktpolitik; Sozialpolitik